Honeydew [videorecording (DVD)] - Milburn, Devereux; Spielberg, Sawyer; Barr, Malin; Kingsley, Barbara; D'Ambrose, Stephen; Dunham, Lena, 1986- (Darkstar Pictures, 2021)
A young couple is forced to seek shelter in the home of an aging farmer and her peculiar son, when they suddenly begin having strange cravings and hallucinations taking them down a rabbit hole of the bizarre.